Peran Tenaga Pendidik Dalam Penanaman Nilai-Nilai Anti Korupsi Di Sekolah Menengah Atas - Pandu Pahlevi; Ilham Fahmi (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to explain the role of educators in instilling anti-corruption values ​​in high school. The method used in this research is descriptive qualitative research with a focus on literature study. Data collection in this study was carried out with books, journals, articles and sources of data or information relevant to the topic of the problem being studied. The data analysis technique includes three stages: data reduction, data display, conclusion drawing/verifying. The results of this study indicate that the role of educators in instilling anti-corruption values ​​in schools can be applied with four approach models, namely: 1) Combination model with curriculum, 2) Model through extracurricular activities, 3) Value habituation model in all student activities, 4 ) Combined models. This approach also supports students in increasing new knowledge so that learning can be effective and efficient and can strengthen the character of students.